2012
DOI: 10.1209/0295-5075/99/40005
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of coupled nonidentical dynamical systems

Abstract: We analyze the stability of synchronized state for coupled nearly identical dynamical systems on networks by deriving an approximate master stability function (MSF). Using this MSF we treat the problem of designing a network having the best synchronizability properties. We find that the edges which connect nodes with a larger relative parameter mismatch are preferred. Also, the nodes having values at one extreme of the parameter mismatch are preferred as hubs where the extreme is the one which gives a better s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…By coupled nearly identical systems we mean systems which have a node dependent parameter (NDP). Preliminary results of this study were earlier reported in [41]. We then extend the MSF formalism to coupled nearly identical systems with degenerate eigenvalues of the coupling matrix.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…By coupled nearly identical systems we mean systems which have a node dependent parameter (NDP). Preliminary results of this study were earlier reported in [41]. We then extend the MSF formalism to coupled nearly identical systems with degenerate eigenvalues of the coupling matrix.…”
Section: Introductionmentioning
confidence: 82%
“…[41], we have extended the formalism of MSF to coupled nearly-identical systems and in this subsection, we briefly review the same. This is done for the sake of completeness and also to establish the notation.…”
Section: A Master Stability Function For Nearly-identical Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to better understand synchronization processes of natural systems it is important to construct a master stability function for generalized synchronization. Motivated by this problem, we have extended the formalism of the master stability function to the generalized synchronization of coupled nearly identical oscillators [8][9][10].…”
Section: Introductionmentioning
confidence: 99%